Retórica e a representação do gênero social feminino na música popular brasileira - Pereira, Cristina Vanessa (2019)
This dissertation is situated in the Critical Discourse Analysis field of sociocognitive level, with Rhetoric. It has as its main objective to contribute to the linguistic studies of feminism in Brazil by means of specific objectives aimed at: 1. Identify the ideological and/or cultural aspects found in the representation of the feminine social gender and its verbal representations; 2. To deal with the interrelationship of text and context in the construction of meanings of representations of the feminine in popular musical lyrics of great circulation; 3. Look for the social roles represented by the feminine social gender in popular lyrics. This research is important because the devaluation of women is still present in Brazilian society despite the advances achieved in the last decades. The analysis carried out followed a theoretical-analytical procedure, whose analytical categories are Society, Cognition and Discourse. To do so, analysis was also based on the notion of context proposed by van Dijk (2012). In this sense, the research adopted the following methodological procedures: 1. Theoretical-analytical procedure: contextualization on the woman over time and theoretical revision on the main concepts of rhetoric and context; 2. Selection of material for analysis: 25 popular songs of great circulation were selected, which were presented as an example of the cultural and ideological values existing in the representation of the feminine. The results indicate that there are values that position the feminine as a gender in society, and these values are linked to a society whose model is patriarchal, which generates prejudice